2010
DOI: 10.1021/jf103335w
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Capsaicin on Human Colon Cancer Cells in Vitro and Colo 205 Tumor Xenografts in Vivo

Abstract: Capsaicin was reported to inhibit cancer cell growth. The aim of this study was to evaluate the antitumor potential of capsaicin by studying antitumor activity in vitro as well as in vivo. The in vitro studies are to examine the effects of capsaicin on human colon cancer colo 205 cells after exposure to capsaicin. The results showed that capsaicin induced cytotoxic effects in a time- and dose-dependent manner and increased reactive oxygen species (ROS) and Ca(2+) but decreased the level of mitochondrial membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(53 citation statements)
references
References 31 publications
6
46
0
1
Order By: Relevance
“…Whereas low ROS levels are involved in normal cell events, excess ROS cause cellular damage and ultimately lead to cell death (Sinha et al 2013). The involvement of ROS in vanilloid-induced apoptosis has been demonstrated in most of the cell lines analyzed (Sanchez et al 2007;Huang et al 2009;Lu et al 2010) and revised by Surh (Surh 2002;Lu et al 2010). In recent years, a number of studies have shown that oxidative stress could cause cellular apoptosis via both the mitochondria dependent and mitochondria-independent pathways (Sinha et al 2013).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas low ROS levels are involved in normal cell events, excess ROS cause cellular damage and ultimately lead to cell death (Sinha et al 2013). The involvement of ROS in vanilloid-induced apoptosis has been demonstrated in most of the cell lines analyzed (Sanchez et al 2007;Huang et al 2009;Lu et al 2010) and revised by Surh (Surh 2002;Lu et al 2010). In recent years, a number of studies have shown that oxidative stress could cause cellular apoptosis via both the mitochondria dependent and mitochondria-independent pathways (Sinha et al 2013).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 97%
“…Sustained elevation in intracellular calcium concentration activates various secondary mechanisms that induce the increased production of reactive oxygen and nitrogen species and ultimately the programmed cell death. Several studies showed that capsaicin-induced apoptosis via increased Ca 2+ levels in different carcinoma cells models (Chou et al 2009;Huang et al 2009;Lu et al 2010), although the molecular mechanisms of the Ca 2+ signaling pathways leading to capsaicin-induced cell death are still misunderstood. The release of intracellular Ca 2+ may be an important regulatory factor on early apoptosis induced by capsaicin as calcium chelators prevent capsaicin-induced cell death (Lee et al 2009).…”
Section: Intracellular Calciummentioning
confidence: 98%
“…It can freely dissolve in organic solvents like alcohol, diethyl ether, phenol, acetone, dioxane, methylbenzene, and aqueous alkali, but to a lesser extent in water at room temperature. CAP is associated with various complicated pharmacological actions such as the prevention and treatment of cardiovascular system diseases (Bencsik et al, 2008), anti-obesity (Joo et al, 2010), and protection of gastrointestinal tract (Szallasi & Blumberg, 1999), as well as antitumor actions (Lu et al, 2010) and analgesia (Menendez et al, 2004). However, lower water solubility and significant first pass effect of liver lead to poor in vivo bioavailability of CAP.…”
Section: Introductionmentioning
confidence: 99%
“…The potent in vitro and in vivo antitumor properties of capsaicin revealed that capsaicin may be used for the treatment of human colon cancer. 19 Oral administration of Crocus sativus carotenoid extract rich extract inhibits the growth of mouse tumors from (sarcoma-180), Ehrlich ascitescarcinoma (EAC), Dalton's lymphoma ascites (DLA) and significantly increased the life spans of treated tumor-bearing mice. 20 Crocetin, the carotenoid constituent of saffron, has shown significant potential as an anti-tumor agent in animal models and cell line systems.…”
mentioning
confidence: 99%